Self-cleaning SiO2/TiO2/PMMA nanocomposite films fabricated by spin coating technique: Effect of different spin speed and film layers - Maneerat Songpanit; Kanokthip Boonyarattanakalin; Saksorn Limwichean; Tossaporn Lertvanithphol; Mati Horprathum; Wisanu Pecharapa; Wanichaya Mekprasart (My University, 2023)
This research aims to develop the self-cleaning efficiency of silicon dioxide/titanium dioxide/methyl methacrylate (SiO2/TiO2/PMMA) nanocomposite films proved by optical and structural properties. The SiO2/TiO2/PMMA nanocomposite films were prepared by spin coating technique with the crucial parameters of spin speed and film layers. The ratio of SiO2:TiO2 in SiO2/TiO2 nanocomposite was conducted at 1:1 by sonochemical process and loading at 1 wt.% in PMMA matrix. Spin speed of SiO2/TiO2/PMMA nanocomposite films in coating process was conducted at 1000, 2000, and 3000 rpm with film growth at 2 layers. Meanwhile, the different film layers of the nanocomposite film were selected as other crucial parameter in spin coating technique and studied at 1, 2, and 3 layers with spin speed 2000 rpm. Surface morphologies, cross-section and element contents of SiO2/TiO2/PMMA nanocomposite films with different spinning speed and film layers were monitored by the photographs, field emission scanning electron microscope (FE-SEM) and energy dispersive X-ray spectroscopy (EDS). Moreover, optical property in transmission mode of SiO2/TiO2/PMMA nanocomposite films was characterized by UV-VIS spectrophotometer. Furthermore, the contact angle measurement o f SiO2/TiO2/PMMA nanocomposite films can identify to hydrophilic properties on the film surface. Therefore, the improvement of self-cleaning property on SiO2/TiO2/PMMA nanocomposite film was occurred by the optimized conditions of spinning speed at 2000 rpm and film growth at 2 layers by spin coat technique.
Keywords: Spin Coating; Titanium Dioxide; Field emission microscopy; Surface Modification and Superhydrophobicity